Filsafat Progresivisme dan Implikasinya Bagi Pendidikan Islam - Sigit Tri Utomo; Luluk Ifadah (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2020)
Abstract: This research is a qualitative study using a library research approach, which is an approach that studies and uses literature as a reference and reference in managing data. This qualitative research as an assessment procedure that produces descriptive data in the form of words written or spoken from someone who can be observed. In this case the object is the relevance of the philosophy of progressivism and its implications for Islamic education. The data collection method in this research uses literature study. In this stage, the researcher tries to select data (books) that are relevant to the philosophy of progressivism and its implications for Islamic education. In this writing, the analysis used with hermeneutics, the writer explains that behind the text there is context meaning or behind the explicit meaning there is an explicit meaning if interpreted literally can be interpreted as an interpretation or interpretation. This method step is intended to capture the meaning, value and purpose of the relevance of the philosophy of progressivism and its implications for Islamic education. Then the authors also use synthesis analysis means the stages of an object of scientific study that connects an articulation of meaning with one another meaning which is then discovered by a new articulation of knowledge in the form of philosophy of progressivism and its implications for Islamic education. The author also uses content analysis, namely research conducted on information documented in recordings, both images, sounds, writing and others. With this method scientific data analysis and processing will be carried out on the content of the philosophy of progressivism and its implications for Islamic education. The results showed that the flow of philosophy of progressivism was the flow of modern educational philosophy which required changes in the implementation of education to be more advanced. This flow of progressivism prioritizes the implementation of education in children-centered schools (student oriented) and makes educators limited to being facilitators, mentors, and directors for students. The purpose of the flow of progressivism in education is to want to change the practice of education that has been impressed authoritarian to be democratic and more respectful of the potential and abilities of children, and encourage the implementation of learning that involves more students. By implementing the flow of progressivism in education, the hope is that it can bring change and progress in education in Indonesia to become more qualified, so that it can realize the goals of Indonesia's national education. Keyword: Philosophy of Progressivism, Islamic Education Abstrak: Penelitian ini merupakan penelitian kualitatif yang menggunakan pendekatan pustaka (library research), yaitu suatu pendekatan yang mengkaji serta mengggunakan literatur sebagai bahan acuan dan rujukan dalam mengelola data. Penelitian kualitatif ini sebagai prosedur penilaian yang menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari seseorang yang dapat diamati. Dalam hal ini objeknya adalah relevansi filsafat progresivisme dan implikasinya bagi pendidikan Islam. Metode pengumpulan data dalam penelitian ini menggunakan studi pustaka. Dalam tahapan ini, peneliti berusaha menyeleksi data-data (buku) yang ada relevansi filsafat progresivisme dan implikasinya bagi pendidikan Islam. Dalam penulisan ini analisis yang digunakan dengan hermeneutika, yakni penulis memaparkan dibalik teks ada makna konteks atau dibalik makna tersurat ada arti tersurat jika diartikan secara harfiah dapat diartikan sebagai penafsiran atau interpretasi. Langkah metode ini dimaksud untuk menangkap arti, nilai dan maksud relevansi filsafat progresivisme dan implikasinya bagi pendidikan Islam. Kemudian penulis juga mengunakan analisis sintesis berarti tahapan terhadap suatu objek kajian ilmiah yang mengaitkan sebiah artikulasi makna satu dengan makna lain yang kemudian ditemukan sebuah pengetahuan dengan artikulasi baru berupa filsafat progresivisme dan implikasinya bagi pendidikan Islam. Penulis juga menggunakan content analysis yaitu penelitian yang dilakukan terhadap informasi yang didokumentasikan dalam rekaman, baik gambar, suara, tulisan dan lain-lain. Dengan metode ini akan dilakukan analisis data dan pengolahan secara ilmiah tentang isi tulisan filsafat progresivisme dan implikasinya bagi pendidikan Islam. Hasil penelitian menunjukkan bahwa aliran filsafat progresivisme merupakan aliran filsafat pendidikan modern yang menghendaki adanya perubahan pelaksanaan pendidikan menjadi lebih maju. Aliran progresivisme ini mengutamakan penyelenggaraan pendidikan di sekolah berpusat pada anak (student oriented) dan menjadikan pendidik hanya sebatas sebagai fasilitator, pembimbing, dan pengarah bagi peserta didik. Adapun tujuan dari aliran progresivisme dalam pendidikan ialah ingin merubah praktik pendidikan yang selama ini terkesan otoriter menjadi demokratis dan lebih menghargai potensi dan kemampuan anak, serta mendorong untuk dilaksanakannya pembelajaran yang lebih banyak melibatkan peserta didik. Dengan menerapkan aliran progresivisme dalam pendidikan, harapannya dapat membawa perubahan dan kemajuan pendidikan di Indonesia menjadi lebih berkualitas, sehingga mampu mewujudkan tujuan pendidikan nasional Indonesia. Kata Kunci: Filsafat Progressivisme, Pendidikan Islam